Chronic intestinal pseudo‐obstruction in children and adults: diagnosis and therapeutic options. Issue 1 (29th September 2016) - Di Nardo, G.; Di Lorenzo, C.; Lauro, A.; Stanghellini, V.; Thapar, N.; Karunaratne, T. B.; Volta, U.; De Giorgio, R.
Abstract: Background: Chronic intestinal pseudo‐obstruction (CIPO) represents the most severe form of gastrointestinal dysmotility with debilitating and potentially lethal consequences. Symptoms can be non‐specific, and result in this condition being diagnosed incorrectly or too late with consequences for morbidity and even mortality. Purpose: The present article aims to provide pediatric and adult gastroenterologists with an up to date review about clinical features, diagnosis and therapeutic options for CIPO. Although pediatric and adult CIPO share many clinical aspects distinctive features can be identified. There is no single diagnostic test or pathognomonic finding of CIPO, thus a stepwise approach including radiology, endoscopy, laboratory, manometry, and histopathology should be considered in the diagnostic work‐up. Treatment of patients with CIPO is challenging and requires a multidisciplinary effort with participation of appropriately experienced gastroenterologists, pathologists, dieticians, surgeons, psychologists, and other subspecialists based on the presence of comorbidities. Current treatment options invariably involve surgery and specialized nutritional support, especially in children. Medical therapies are mainly aimed to avoid complications such as sepsis or intestinal bacterial overgrowth and, where possible, restore intestinal propulsion. More efficacious therapeutic options are eagerly awaited for such difficult patients. Abstract : Chronic intestinal pseudo‐obstruction (CIPO) represents the most severe form of gastrointestinal dysmotility with debilitating and potentially lethal consequences. Symptoms can be non‐specific, and result in an incorrect or too late diagnosis with consequences in terms of morbidity and even mortality. Thus, the present article aims to provide pediatric and adult gastroenterologists with an up to date review about clinical features, diagnosis, and therapeutic options for CIPO.